DEMOKRASI INDONESIA: MENGUJI VALIDITAS DALAM TAKARAN FALSIFIKASI POPPER - Yohanes Baptista Angelino Galus (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Democracy in Indonesia, particularly in the context of a pluralistic society, faces significant challenges related to the weakening of its core values, such as popular sovereignty, political participation and transparency. Indonesia's declining democracy index, as reported by Democracy Index 2023, reflects problems such as corruption, weak government accountability, and lack of space for criticism. In an effort to strengthen democracy, Karl Popper's falsification theory is relevant as an epistemic paradigm to encourage transparency and critical examination of public policies. The principle of falsification, which prioritizes criticism and testing of truth claims, is in line with Pancasila democracy which emphasizes deliberation for consensus. The purpose of writing this article is to examine the validity of democratic practices in Indonesia in terms of Karl Popper's falsification theory. The method used in writing this article is a qualitative library method by searching for books as primary sources and articles as secondary sources. The results found in writing this article are that falsification emphasizes the importance of error as a means of correction, so that public policy must always be open to rational criticism for continuous improvement. However, the practice of democracy in Indonesia is often hampered by ideological absolutism, the dominance of certain doctrines, and the resistance of public officials to criticism, all of which weaken the mechanisms of deliberation and inclusiveness. Therefore, the principle of falsification can serve as an epistemological correction tool to deepen the democratic values of Pancasila, by directing policies towards rationality, active participation of society, and respect for plurality, so that democracy can evolve towards a more inclusive and ethical maturity.